PEMBERDAYAAN MASYARAKAT TENTANG TUMBUH KEMBANG ANAK PAUD/TK HOLISTIK DI PUSKESMAS PRUMNAS REJANG LEBONG BENGKULU - yenni puspita yenni; Indah Fitri Andini (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Toddler period is known as the "golden period" and "window of opportunity", a period that is very sensitive to the environment and cannot be repeated. Efforts are made for children to grow and develop optimally by detecting deviations and early intervention. PAUD / Kindergarten teachers are an important element who can find out the existence of growth and development deviations and appropriate interventions at an early age. Community service activities aim to empower PAUD/TK teachers in increasing knowledge and skills through training for PAUD/TK teachers in stimulating children's growth and development and implementing SDIDTK to increase growth and development of preschool/kindergarten children. The target of the activity is 35 PAUD/TK teachers in the Working Area of the Prumnas Public Health Center, Rejang Lebong Regency in 2021. Training activities are carried out offline. The results of the pre-test and post-test of participants showed an increase in knowledge of 27.0 and the results of skills assessment using a checklist obtained an average score of 87. Community service activities by empowering PAUD/TK teachers through training and mentoring so as to improve the knowledge and skills of PAUD/TK teachers in conducting stimulation and early detection of growth and development of kindergarten/early childhood children.